2009
DOI: 10.1080/87565640903265145
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Low Neonatal Iron Status Due to Maternal Diabetes Mellitus on Explicit Memory Performance in Childhood

Abstract: Diabetic pregnancies are characterized by chronic metabolic insults, including iron deficiency, that place the developing brain at risk and for memory impairment later in life. A behavioral recall paradigm coupled with electrophysiological measures was used to assess the longevity of these effects in 40 3½-year-old children. When memory demands were high, recall was significantly impaired in the at-risk group and correlated with perinatal measures of iron. Electrophysiological results suggested both encoding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 57 publications
(110 reference statements)
5
81
1
2
Order By: Relevance
“…In relation to memory tasks, poor performance by infants born to gestational diabetes mothers in auditory recognition memory at birth, 26 visual recognition memory at 6 months, 27 cross-modal memory at 8 months, 28 and delayed recall at 12 months, 29 as well as lower performance on immediate recall and delayed recall on tasks with high memory demands at 3½ years of age, 30 have all been reported previously. A recent study that included only gestational diabetes children reported lower performance at 6 months on recognition memory assessed by a Visual Habituation paradigm, but not on short memory at 60 months.…”
Section: Discussionmentioning
confidence: 80%
“…In relation to memory tasks, poor performance by infants born to gestational diabetes mothers in auditory recognition memory at birth, 26 visual recognition memory at 6 months, 27 cross-modal memory at 8 months, 28 and delayed recall at 12 months, 29 as well as lower performance on immediate recall and delayed recall on tasks with high memory demands at 3½ years of age, 30 have all been reported previously. A recent study that included only gestational diabetes children reported lower performance at 6 months on recognition memory assessed by a Visual Habituation paradigm, but not on short memory at 60 months.…”
Section: Discussionmentioning
confidence: 80%
“…In contrast to adults, however, early life ID populations continue to demonstrate wide-ranging learning and memory deficits following iron repletion. For example, 3.5-yold children who had been iron deficient at birth exhibited impaired recall memory during elicited imitation tasks and their degree of learning and memory impairment was directly correlated to the degree of ID at birth (8). At 5 y of age, children who were born with low iron stores showed decreased language development, fine motor skills, and tractability relative to children with normal iron stores at birth (22).…”
Section: Current State Of Knowledgementioning
confidence: 97%
“…In humans, early life ID (i.e. late gestation through 2-3 y of age) results in learning and memory deficits that persist beyond the period of ID despite prompt iron treatment (7)(8)(9), findings supported by rodent models of early ID anemia (IDA) (10,11). There are at least 2 types of memory: declarative (or explicit) and nondeclarative (or implicit) (12).…”
Section: Introductionmentioning
confidence: 97%
“…While diabetes mellitus during pregnancy confers multiple risks to fetal neurodevelopment besides iron deficiency (e.g., hypoglycemia and hypoxia), these factors were controlled for in this series of studies [40]. In 3.5-year-olds whose neonatal ID had resolved, those with lower serum ferritin concentrations at birth had poorer immediate, delayed, and working memory [41]. * Indeed, the poorness of their performance was directly related to their degree of neonatal ID.…”
Section: Observational Studies Of Fetal/neonatal Idmentioning
confidence: 99%